Stem Cell Therapy for Neurodegenerative Diseases: How Do Stem Cells Bypass the Blood-Brain Barrier and Home to the Brain? - Yvonne Cashinn Chia; Clarice Evey Anjum; Hui Rong Yee; Yenny Kenisi; Mike K. S. Chan; Michelle B. F. Wong; Shing Yi Pan (Hindawi Limited, 2020)
Blood-brain barrier (BBB) is a term describing the highly selective barrier formed by the endothelial cells (ECs) of the central nervous system (CNS) homeostasis by restricting movement across the BBB. An intact BBB is critical for normal brain functions as it maintains brain homeostasis, modulates immune cell transport, and provides protection against pathogens and other foreign substances. However, it also prevents drugs from entering the CNS to treat neurodegenerative diseases. Stem cells, on the other hand, have been reported to bypass the BBB and successfully home to their target in the brain and initiate repair, making them a promising approach in cellular therapy, especially those related to neurodegenerative disease. This review article discusses the mechanism behind the successful homing of stem cells to the brain, their potential role as a drug delivery vehicle, and their applications in neurodegenerative diseases.